Performance Improvement of Hydraulic Excavator Efficiency: A Literature Review - Geralda Livia Nugraha; Muhamad Ajis; Himmawan Sapta Adhi; Diky Zakaria (Journal of Mechatronics and Artificial Intelligence, 2024)
Excavators dominate heavy-duty jobs worldwide.  As a major construction machine, their enhanced productivity in work has led to a strong demand for them. Concerns for the environment, increased efficiency, and energy conservation all reflect this goal. Several studies on these matters Automation in construction equipment, particularly hydraulic excavators, has gained popularity among producers and academics. This article examines articles about environmental concerns, efficiency enhancements, and energy (storage and evolving) issues in hydraulic excavators from a number of databases. This article reviews the technology of hydraulic excavators, covering their performance, related components, energy use, efficiency, and future opportunities. Research questions addressed include: How do hydraulic excavators work, what are the components, what is the role of maintenance in maintaining the performance of hydraulic excavator systems, what are the latest innovations in development for hydraulic excavator systems that can improve efficiency and reliability, and how can new technologies help reduce the impact on the environment. The method used to answer the research questions is SLR. The results of this article illustrate that excavator efficiency and performance depend on the architecture of the component layout, technology, systems and operational machinery used. The energy regeneration system serves to capture and store the potential energy generated during excavator operation. This stored energy can be reused to help power the hydraulic system, reducing the need for additional energy input.